CULTURE-BASED EDUCATION IN TONGKONAN CONSTRUCTION ACTIVITIES - Dendo, Ermitha Ambun Rombe; Ampangallo, Bastian artanto; Arrang, Abdias Tandi; Masiku, Henrianto (Yayasan Literasi Kita Indonesia, 2024)
This study explores the integration of culture-based education into the construction activities of Tongkonan, traditional Torajan ancestral houses in Indonesia. Tongkonan not only serve as architectural marvels but also embody cultural values, social structures, and ancestral heritage. The research examines how incorporating cultural education into the construction process can enhance both the preservation of traditional practices and the educational outcomes for participants. By analyzing case studies of Tongkonan construction projects, the study identifies key pedagogical strategies that leverage cultural narratives, traditional craftsmanship, and community rituals. Findings suggest that such an approach fosters a deeper appreciation for cultural heritage, improves skill acquisition, and strengthens communal bonds. The study concludes with recommendations for educational frameworks that integrate cultural elements into construction training programs, aiming to sustain both the physical and intangible heritage of the Torajan people.